Role of budgeting as a planning instrument in control system by the company of holding type. (Journal of Economic Research & Business Administration, 2016)
Nowadays, one the instruments key of management and planning, providing intercommunication of strategy of company with the short-term tasks of separate subdivisions, technology of budgeting is. Presently in Kazakhstan counted the row of holding type companies, which have the working systems of budgeting and greater amount gathers to realize projects on their introduction in the near time. However, not at all in all cases those companies use the systems of budgeting count up a benefit from the facilities inlaid in a project already now. It is possible to say so, that their system of budgeting is not to the end debugged and requires a revision. Many holding of our country have row of problems, impedimental not to only the literate drafting of budgeting but also development of company overall. In this article given classic problems over of budget forming in the process of management holding and ways of their decision.
Keywords: budgeting; planning; holding; instrument of planning; problem of budgeting; system of budgeting; budgeting technology.